A variable parameters damage model for concrete. (1st April 2020) - Qi, Huijun; Li, Tongchun; Liu, Xiaoqing; Zhao, Lanhao; Lin, Chaoning; Fan, Shujie
Highlights: A variable parameters constitutive model of concrete is proposed. This model reflects progressive failure progress of concrete. This model can more conducive to analysis multi-axial stress state. This model can reflect the stress drop in the descending section better. Abstract: A novel four-parameters damage constitutive model for concrete in strain space is proposed in this paper. It is based on the Heish-Ting-Chen constitutive model and is derived in the framework of the thermodynamics of irreversible process. Because tension damage is a major fracture mode in concrete used for hydraulic structures, an equivalent strain is introduced that converts the multi-axial strain state into the equivalent tension strain to determine the tension damage. Considering the change in the equations' parameters during progressive failure, a variable parameters constitutive model is established. The parameters of the damage constitutive model are obtained by the increasing section and the decreasing section of stress-strain curve and it is demonstrated that the proposed model performs better than the regular constitutive model in the decreasing section. The numerical implementations provide a good description of the failure process as well as an accurate prediction of the behaviour of concrete.